Analisis Perbandingan Kinerja Keuangan antara Bank Konvensional dan Bank Syariah - Saputri, Indiani; Wahyu, Wulan; Sari, Nurma (Jurnal KIAFE, 2026)
This study aims to examine differences in financial performance between conventional and Islamic banking by comparing PT Bank Central Asia Tbk and BCA Syariah during the 2018–2023 period. The research focuses on profitability, intermediation, and operational efficiency measured using Return on Assets, Loan to Deposit Ratio or Financing to Deposit Ratio, and Operating Expenses to Operating Income. This study employs a quantitative descriptive-comparative approach using secondary data obtained from the banks’ financial statements. Data normality was tested using the Kolmogorov-Smirnov and Shapiro-Wilk tests, while mean differences were analyzed using independent samples t-tests at a significance level of 0.05. The results show that BCA has a higher average Return on Assets than BCA Syariah, indicating stronger profitability. BCA also has a lower Operating Expenses to Operating Income ratio, indicating better operational efficiency. Meanwhile, BCA Syariah has a higher Financing to Deposit Ratio than BCA’s Loan to Deposit Ratio, indicating more aggressive fund intermediation. All differences are statistically significant. These findings suggest that BCA outperforms BCA Syariah in profitability and efficiency, while BCA Syariah requires careful liquidity risk management due to its higher fund distribution ratio.